Improving Legal Culture is the Foundation of Our Future - Abdurakhmanova Nodirakhan Khusnutdinovna (Global Scientific Publishing, 2023)
This article explores the critical role of improving legal culture as the foundational element for the future development of Uzbekistan. Legal culture, encompassing attitudes, values, and understanding of legal principles within society, is a cornerstone for fostering justice, social harmony, and economic progress. The article investigates ongoing initiatives, educational reforms, and community engagement strategies aimed at enhancing legal awareness and promoting a culture of compliance with the law. By recognizing the pivotal importance of legal culture, this article contributes to the broader discourse on nation-building, emphasizing its significance in shaping a sustainable and just future for Uzbekistan.
Keywords: Legal culture; Legal awareness; Rule of law